Practical education at the Sopron Kindergarten Training Institute in the early 70s (Training and Practice : Journal of Educational Sciences, 2020)
Below we would like to introduce the characteristics of practical training at the Sopron Kindergarten Training Institute during the first few years of the 1970s. Higher education, including teacher and kindergarten educations, underwent major reforms in 1970. On the basis of guidelines issued by the Teacher Training Department of the Ministry of Education, the practical education of the students participating in teacher training has been transformed. The research will use institutional and national documents regulating practical education and guides issued and approved by practitioners. We would like to contribute our research to a thorough understanding of the history of Hungarian kindergarten teacher education, paying tribute to the precious merits of the predecessors sacrificial work at the Sopron Kindergarten Teacher Training Institute.